The Impasse of the Latin American Left - Gaudichaud, Franck; Webber, Jeffery R.; Modonesi, Massimo, 1971- (Book collections on Project MUSE., 2022)
"At the turn of the twenty-first century, Latin American politics were marked by an upsurge in progressive movements, as popular uprisings for land and autonomy in the later 90s and early 2000s led to election of left and center-left governments in Venezuela, Brazil, Argentina, Bolivia, Uruguay, Ecuador, Nicaragua, and El Salvador. Impasse of the Latin American Left explains the ascent, consolidation, and crisis of the contemporary Latin American Left's political experiences, from the rise of social movements in the 1990s, through the height of the electoral Pink Tide and the commodities boom of the 2000s, to the regional crises of economic stagnation and the COVID-19 pandemic in recent years"--